Enhancing butanol separation efficiency in pervaporation with ZIF-8 porous liquid infused mixed matrix membranes - Komal, Ayesha; Kasuri, Amna; Yasin, Muhammad; Khan, Asim Laeeq; Razzaq, Abdul; Alhmohamadi, Hamad; Akhtar, Faheem Hassan; Raja, Arsalan Ahmad; Nawaz, R.; Abdulmalek, Emilia; Gilani, Mazhar Amjad (Elsevier BV, 2024)
Separating butanol/water mixtures via distillation is notably energy-intensive and costly, highlighting the urgent need for more efficient alternatives. This study introduces a novel approach using mixed matrix membranes (MMMs) infused with Zeolitic Imidazolate Framework-8 (ZIF-8) transformed into its porous liquid (PL) form, aimed at enhancing the separation efficiency of butanol/water mixtures through pervaporation (PV). We selected ZIF-8 for its hydrophobic nature and high surface area, which are critical for improving both flux and selectivity in membrane-based separation processes. The study details the synthesis of ZIF-8-PL, its characterization through techniques such as Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM), and the fabrication of the MMMs. Our results demonstrate that ZIF-8-PL-based membranes at 55°C with a 30 wt% PL loading significantly enhance biobutanol-selective PV efficiency. Specifically, these membranes show an improvement in flux of approximately 102% and an increase in separation factor by 64% when compared to unmodified polydimethylsiloxane (PDMS) membranes. This significant enhancement highlights the effectiveness of PL-based fillers in advancing MMM performance for biofuel separation, providing a promising route to optimize energy efficiency and cost-effectiveness in industrial scale applications.